2020
DOI: 10.1302/0301-620x.102b6.bjj-2019-1596.r1
|View full text |Cite
|
Sign up to set email alerts
|

2020 Mark Coventry Award: Microorganism-directed oral antibiotics reduce the rate of failure due to further infection after two-stage revision hip or knee arthroplasty for chronic infection: a multicentre randomized controlled trial at a minimum of two years

Abstract: Aims The aim of this study was to determine if a three-month course of microorganism-directed oral antibiotics reduces the rate of failure due to further infection following two-stage revision for chronic prosthetic joint infection (PJI) of the hip and knee. Methods A total of 185 patients undergoing a two-stage revision in seven different centres were prospectively enrolled. Of these patients, 93 were randomized to receive microorganism-directed oral antibiotics for three months following reimplantation; 88 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 30 publications
1
51
1
4
Order By: Relevance
“…In addition to a thorough history and physical examination, the diagnosis of PJI often relies on serological tests and radiographic evaluation [ 6 ]. In particular, isolating the infecting microorganism from cultures of fluid or tissue within the joint remains the cornerstone for diagnosis and targeted antibiotic therapy, which has been shown to increase the chances of treatment success [ 7 ]. This also provides valuable prognostic information for patients and guides perioperative counseling [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to a thorough history and physical examination, the diagnosis of PJI often relies on serological tests and radiographic evaluation [ 6 ]. In particular, isolating the infecting microorganism from cultures of fluid or tissue within the joint remains the cornerstone for diagnosis and targeted antibiotic therapy, which has been shown to increase the chances of treatment success [ 7 ]. This also provides valuable prognostic information for patients and guides perioperative counseling [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have concluded that following stage II reimplantation, the use of two to three days of standard antibiotic prophylaxis can achieve infection control rates equivalent to four to six weeks of antibiotic use, 18-20 but studies with higher levels of evidence have found that extending antibiotic treatment to three months was beneficial for infection control. 7,8 The RCTs showed that extended antibiotics should be used, thus raising a new question: if antibiotics use needs to be extended, for how long should they be used? Therefore, our study divided patients into a short course of extended antibiotic treatment (mean 20.17 days (SD 5.30)) and a long course of extended antibiotic treatment (mean 45.02 days (SD 15.03)) and found infection control rates of 95.3% and 92.7% for the short course and long course groups, respectively, with no statistically significant difference (p = 0.676, Fisher’s exact test).…”
Section: Discussionmentioning
confidence: 99%
“…The overall infection control rate was 94.3% (99/105) in this study, which was at a high level compared to previous studies. 8,17,21,22 This may be related to the comprehensive use of tissue culture technology, 23 ultrasonic lysis technology, and metagenomic next-generation sequencing 24,25 to improve pathogen identification. The high detection rate of pathogens and clear drug susceptibility in the involved cases made the application of antibiotics more appropriate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Furthermore, recent studies have shown that administration of postoperative oral antibiotics to patients undergoing revision surgery resulted in lower rates of infection. 30 , 31 The sparse evidence that exists recommends that a broad-spectrum antibiotic should be included in the perioperative prophylaxis along with flucloxacillin. 32 …”
Section: Discussionmentioning
confidence: 99%